Dkk‐3 is elevated in CSF and plasma of Alzheimer’s disease patients - Zenzmaier, Christoph; Marksteiner, Josef; Kiefer, Andreas; Berger, Peter; Humpel, Christian (Journal of neurochemistry, 2009)
Biomarkers in CSF can offer improved diagnostic accuracy for Alzheimer’s disease (AD). The present study investigated whether the glycoprotein and putative tumor suppressor Dickkopf homolog 3 (Dkk‐3) is secreted into CSF and evaluated its applicability as a diagnostic marker for AD. Using our highly specific immunoenzymometric assay, Dkk‐3 levels were measured in plasma and/or CSF of patients suffering from depression, mild cognitive impairment (MCI), or AD and compared with healthy subjects. Dkk‐3 identity was verified by western blot and matrix‐assisted laser desorption/ionization time‐of‐flight (MALDI‐TOF) mass spectrometry (MS)/MS. High concentrations of Dkk‐3 were detected in CSF compared with plasma (28.2 ± 1.3 vs. 1.22 ± 0.04 nmol/L, respectively). Consistently Dkk‐3 expression was demonstrated in neurons of the cortex and epithelial cells of the choroid plexus, the major source of CSF. Significantly increased Dkk‐3 levels in plasma and CSF were observed for AD patients compared with healthy subjects but not patients suffering from MCI or depression. In summary, our data indicate that elevated Dkk‐3 levels are specifically associated with AD and might serve as a potential non‐invasive AD biomarker in plasma.